ANALYSIS ON READING-BASED RESEARCHES CONDUCTED IN ENGLISH EDUCATION STUDY PROGRAM - Syaiful, Muhammad; salam, Urai; Buan, Stevanus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract:This research entitled analysis on reading-based researches conducted in english education study program. The purpose of this research is to investigate reseachers’ interest on reading skill in thesis writing. The subjects of research are the theses written on reading interest by English Education Study Program during the period 2006-2011.The research data are taken from UPT PerpustakaanTanjungpura University. The data were analyzed by descriptive study by classified into several categories of interest: Method of Research, Research Focus, Research venue.As the result, mostly theses used Pre-experimental Study. It was 71,74% of the samples while Classroom Action Research and Descriptive Study are 19,56% and 8,70%. According to the research focus: teaching technique is 78,26 %, teaching media is 17,39% and unclassified 4,35%. Researchers’ interest based on venue of study; Elementary School (4,35%), Junior High School (36,96%), Senior High School (52,17%) and University (6,52%). Keywords: Thesis, Researchers’ Interest, Reading Skill Abstrak: Penelitian ini berjudul Analisis pada penelitian berbasis membaca yang dilakukan di Program Studi Pendidikan Bahasa Inggris. Tujuan dari penelitian ini adalah untuk menginvestigasi ketertarikan penulis pada kemampuan membaca dalan penulisan tesis. Subjek penelitian adalah tesis yang ditulis dalam ketertarikan kemampuan membaca oleh Program Studi Pendidikan Bahasa Inggris selama periode 2006-2011. Data penelitian ini diambil dari UPT Perpustakaan Universitas Tanjungpura.Data penelitian dianalisismenggunakan studi deskripsi dengan mengklasifikasikan ke dalam beberapa kategori ketertarikan; Metode Penelitian, Fokus Penelitian dan Tempat Penelitian. Sebagai hasilnya, sebagian besar tesis menggunakan Studi Pra-eksperimen. Studi ini mencapai 71,74% dari seluruh subjek penelitian. Sementara Penelitian Tindakan dan Studi Deskripsi adalah 19,56% dan 8,70%. Berdasarkan Fokus Penelitian; Teknik Pembelajaran 78,26%, Media Pembelajaran 17,39 % dan bukan Keduanya 4,35 %. Ketertarikan terhadap Tempat Penelitian; Sekolah Dasar (4,35 %), Sekolah Menengah Pertama (36,96%), Sekolah Menengah Atas (52,17%) and Universitas(6,52%). Kata Kunci: Tesis, KetertarikanPeneliti, Kemampuan Membaca